A propensity score analysis of a community resettlement programme for women prisoners. (February 2019) - Sutherland, Alex
This article presents results from a quasi-experimental evaluation of a prisoner resettlement project for women offenders. Overall the results show that there was no statistically discernible difference in the proven reoffending rate; but frequency of proven reoffending was higher for women who participated in the project compared to the matched comparison group. The approach taken here has broad relevance for those providing services in the community to offenders, as well as government agencies pushing through large-scale reforms to criminal justice as part of the Transforming Rehabilitation agenda. In mimicking the Ministry of Justice Datalab's approach, this article also lays bare the strengths and limitations of this method when applied to interventions run by community organizations. Further implications for policy and research are discussed in the conclusion.